Application of a master meter systemto assure crude oil and natural gas quality during transportation. (18th August 2018) - Perisic, Jasmina; Milovanovic, Marina; Petrovic, Ivana; Radovanovic, Ljiljana; Ristic, Marko; Speight, James G.; Perisic, Velimir
ABSTRACT: This paper discusses an example of the master meter system (MMS), used in the oil and gas industry with the purpose of validating the performance of custody transfer meters. The system can also be used to determine if there are any changes such as the deposition of wax or asphaltic material (in the case of crude oil) or liquids (in the case of natural gas). According to current standards, custody transfer measurements must pass periodic verification of measurement performance, the process which is known as meter proving. This paper presents the construction and key parts, as well as the main functionalities of MMS which comply with the most rigorous requirements for custody transfer. This is achieved by using a novel instrumentation with high level of accuracy, appropriate flow computer and HMI (Human Machine Interface) application developed to support supervision and control of the proving process.